Improved Ability to Compose Arabic Sentences Using the Hot Potatoes Application - Mutmainah, Ismul; Ahmadi, Ahmadi; El Bilad, Cecep Zakarias; Ilmiani, Aulia Mustika (Journal Of Foreign Language Learning and Teaching, 2022)
Ismul Mutmainah, 2021, The Effectiveness of Using Hot Potatoes Applications in Improving the Ability to Arrange Arabic Sentences in Mts. Istiqamah Muara Teweh. Department of Language Education, Faculty of Tarbiyah and Teacher Training, at IAIN Palangka Raya, Advisor (1) Dr. Ahmadi, M.Pd. Supervisor (2) Cecep Zakarias El Bilad, M.Pd.This study aims to determine the effectiveness of the use of the Hot Potatoes application in improving students' ability to compose Arabic sentences. This study uses a quantitative research method of experimental type or a true experimental design using a pretest-posttest control group design. The sample in the study was class VII students at Madrasah Tsanawiyah Istiqamah Muara Teweh. From this study, the following results were found: 1. Students in the control class and Students from the experimental class show an increase in their ability to compose sentences seen from the average value of the pretest and posttest results. So, it can be concluded that the Hot Potatoes application can improve students' ability to compose sentences. 2. The comparison of the posttest mean scores of the experimental class and the control class using the independent sample test, obtained a significance value of 0.020 which is smaller than 0.05, so there is a significant difference in learning outcomes between experimental class students who learn to use the Hot Potatoes application with control class students who do not use the Hot Potatoes application. The Hot Potatoes application was more effective for students in this study.